2022
DOI: 10.1007/s11356-022-18978-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lean manufacturing tools on sustainability: the case of Mexican maquiladoras

Abstract: The Mexican maquiladora industry is applying Lean Manufacturing Tools (LMT) in its production lines; however, few studies have investigated its relationship with sustainability (social, economic, and environmental). This paper presents a second-order structural equation model (SEM) relating 8 LMT integrated into three independent latent variables: continuous improvement (Kaizen and Gemba), supporting tools (Andon, visual management, and Poka-yoke), and machinery and equipment (total productive maintenance, ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 75 publications
2
11
0
1
Order By: Relevance
“…Only the direct link between lean implementation and environmental performance is investigated in this study. The results of this study showed that adopting lean tools directly impacts environmental performance in a positive or negative way, which is consistent with studies by Galeazzo et al (2014), Hopp and Spearman (2004), Taucean et al (2019), Hassan andPasha (2022), andGarciaAlcaraz et al (2022), but not Thekkoote (2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Only the direct link between lean implementation and environmental performance is investigated in this study. The results of this study showed that adopting lean tools directly impacts environmental performance in a positive or negative way, which is consistent with studies by Galeazzo et al (2014), Hopp and Spearman (2004), Taucean et al (2019), Hassan andPasha (2022), andGarciaAlcaraz et al (2022), but not Thekkoote (2022).…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, lean allegedly accidentally enhances environmental performance, according to Galeazzo et al (2014), Hopp and Spearman (2004), Hassan andPasha (2022), andGarciaAlcaraz et al (2022). In other words, the use of lean tools causes lean implementation to have direct, positive, or negative effects on environmental performance.…”
Section: The Impact Of Lean Implementation On Enterprise's Environmen...mentioning
confidence: 99%
“…In general terms, Shafiq and Soratana [ 48 ] indicate that LM implementation represents an economic investment that managers do not want to risk; however, they point out that the main problem is ESU preparation. Specifically, García-Alcaraz et al [ 15 ] relate 8 LM tools to Mexican maquiladora companies’ industrial sustainability and indicate that ESU requires high investments and LM.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Also, it has been observed that many studies have been conducted in different countries, such as Brazil [ 9 ], Spain and Italy [ 10 ], Thailand [ 11 , 12 ], Spain and Portugal [ 13 ], and India [ 14 ]. However, few studies have been carried out on this topic in Mexico, and those that exist are limited to analyzing isolated LM tools [ 8 , 15 ]. However, the LM implementation implies that several tools are applied simultaneously in a production line and that there is a sequence and dependence between them; for example, OEE depends on the efficiency of the implemented TPM programs.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Arredondo-Soto et al [24] analyzed how machinery and equipment calibration can reduce costs and increase economic sustainability. Recently, García-Alcaraz et al [25] reported the relationship between improvement techniques such as kaizen, Gemba, and some visual LM tools with economic sustainability in maquiladoras established in Ciudad Juarez (Mexico). In conclusion, there is evidence that LMTs are related to sustainability, but the experience of Mexican maquiladora is not reported in depth.…”
Section: Introductionmentioning
confidence: 99%